SELECTED FACTORS RELATED TO STRESS OF THE NEW TROOPS AT A MILITARY TRAINING UNIT IN THE NORTHEASTERN REGION - Pholkrathok, Pornthip; Tosangwarn, Suhathai (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This descriptive correlational study aimed to examine the stress, resilience quotient, self-esteem, and the relationships between resilience quotient and self-esteem with the stress of new troops. The participants consisted of 280 new troops in the first shift of the year 2024 at a military training unit in the Northeastern region. Multi-stage random sampling was used to select the participants. The research instruments consisted of a Thai Perceived Stress Scale-10, Resilience Quotient, and Thai version of Rosenberg Self-Esteem Scale, which had Cronbach’s alpha coefficients of .84, .89, and .72 respectively. Data was analyzed using descriptive statistics and Pearson’s product-moment correlation. The research results found that most new troops had moderate levels of stress (70.72%), resilience in the normal range (57.86%), and moderate levels of self-esteem (73.57 %). It was also found that resilience and self-esteem were negatively significantly related to stress at the .05 level (r= -.340 and -.473, p< .05). The results of this study could be used as a guideline to develop methods for promoting new troops to strengthen their mental resilience and self-esteem to reduce stress in this population.